Human rights : moral or political? - Etinson, Adam, 1982- (Oxford, United Kingdom : Oxford University Press, 2018)
"Human rights have a rich life in the world around us. Political rhetoric pays tribute to them, or scorns them. Citizens and activists strive for them. The law enshrines them. And they live inside us too. For many of us, human rights form part of how we understand the world and what must (or must not) be done within it. The ubiquity of human rights raises questions for the philosopher. If we want to understand these rights, where do we look? As a set of moral norms, it is tempting to think they can be grasped strictly from the armchair, say, by appeal to moral intuition. But what, if anything, can that kind of inquiry tell us about the human rights of contemporary politics, law, and civil society - that is, human rights as we ordinarily know them? This volume brings together a distinguished, interdisciplinary group of scholars to address philosophical questions raised by the complex status of human rights as both moral rights, on the one hand, and legally, politically, and historically practised rights, on the other. Its original chapters, each accompanied by a critical commentary, explore topics including: the purpose and methods of a philosophical theory of human rights; the "Orthodox-Political" debate; the relevance of history to philosophy; the relationship between moral and legal human rights; and the value of political critiques of human rights."--
The relevance of history -- The orthodox-political debate -- Morality and law -- Ideals and their limits -- The challenges of politics -- Individuals, borders, and groups.
Includes bibliographical references and index.
Keywords: Human rights; Human rights; 86.81 human rights; 08.45 political philosophy